If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3) * 2x + -1(2) * 7 = (4) * 3x + -1(3) * 8 Multiply 3 * 2 6x + -1(2) * 7 = (4) * 3x + -1(3) * 8 Multiply -1 * 2 6x + -2 * 7 = (4) * 3x + -1(3) * 8 Multiply -2 * 7 6x + -14 = (4) * 3x + -1(3) * 8 Reorder the terms: -14 + 6x = (4) * 3x + -1(3) * 8 Multiply 4 * 3 -14 + 6x = 12x + -1(3) * 8 Multiply -1 * 3 -14 + 6x = 12x + -3 * 8 Multiply -3 * 8 -14 + 6x = 12x + -24 Reorder the terms: -14 + 6x = -24 + 12x Solving -14 + 6x = -24 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -14 + 6x + -12x = -24 + 12x + -12x Combine like terms: 6x + -12x = -6x -14 + -6x = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 -14 + -6x = -24 + 0 -14 + -6x = -24 Add '14' to each side of the equation. -14 + 14 + -6x = -24 + 14 Combine like terms: -14 + 14 = 0 0 + -6x = -24 + 14 -6x = -24 + 14 Combine like terms: -24 + 14 = -10 -6x = -10 Divide each side by '-6'. x = 1.666666667 Simplifying x = 1.666666667
| ((12x^2y)/(4z^4))((-25x^2z^3)/(-15y^2)) | | 4x*4-5x-3-6x+4-2x*2= | | -5p=-35 | | 32-4h-h^2=0 | | 3x*2.5x= | | 9x-2y+10=0 | | 9n^2-21n=-10 | | 7x^2+7x-1=0 | | 4x=1/3=11 | | -a^2-18-9a=0 | | 15+.75x=.8x | | -2/5*5/2 | | -3k(k^(7/5)-4k^(4/5) | | 89+29= | | 3x/4-1=4-7x/8 | | 4x=.3333333333 | | -36=-26y | | 35+.08m=25+.25m | | 6-4(5-3x)=0 | | 7(a+2)=11a+17-7a | | 3(2m+5)+m=-5(3m-3) | | 6-4(2x+9)=5 | | 40=20log(x) | | 3-49+-1*3=x | | (3/2)(x-9)=-5 | | 100=20log(x) | | y/4-y/3=1/6 | | (9/5)(-6x-3)=1 | | (9/5)(-6x-3)=1 | | (9/5)(-6x-3)=1 | | 12(x+1)-(-9x-3)=x-9+3 | | u^2-8-7u=0 |